THE EFFECT OF PROFITABILITY AND COMPANY SIZE ON INCOME SMOOTHING (Study on Banking Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2021 Period) - Rozan Muhammad Daffa; Sendi Gusnandar Arnan (Jurnal Ekonomi, 2022)
This influence aims to determine whether profitability and company size have partial and simultant on the possibility of income smoothing practices in banking sector companies listed on the Indonesia Stock Exchange for the period 2019-2021. The factors tested in this study were profitability and company size as independent variables, while income smoothing as the dependent variable. The research method used in this study was an quantitative descriptive analysis method. The population in this study are banking sector companies listed on the Indonesia Stock Exchange for the period 2019-2021, totaling 46 companies. Sampling technique used in this study was non probability sampling with purposive sampling method, the number of samples was 29 companies. Data analysis used in this study was panel data regression analysis at a significance level of 5%. The program used in analyzing data was SPSS. The results of the study showed that profitability had a influence on income smoothing. Company size had a influence on income smoothing. Company size and profitability simultaneously had a influence on income smoothing.